Tentative identification of volatile flavor compounds in commercial budu, a Malaysian fish sauce, using GC-MS - Mohamed, Hajaratul Najwa; Che Man, Yaakob; Mustafa, Shuhaimi; Abd Manap, Mohd Yazid (MDPI, 2012)
Budu is a famous Malaysian fish sauce, usually used as seasoning and condiment in cooking. Budu is produced by mixing fish and salt at certain ratio followed by fermentation for six months in closed tanks. In this study, four commercial brands of Budu were analyzed for their chemical properties (pH, salt content and volatile compounds). The pH of Budu samples ranged from 4.50–4.92, while the salt (NaCl) content ranged between 11.80% and 22.50% (w/v). For tentative identification of volatile flavor compounds in Budu, two GC columns have been used, DB-WAX and HP-5MS. A total of 44 volatile compounds have been detected and 16 were common for both columns. 3-Methyl-1-butanol, 2-methylbutanal, 3-methylbutanal, dimethyl disulfide, 3-(methylthio)-propanal, 3-methylbutanoic acid and benzaldehye have been identified as the aroma-active compounds in Budu due to their lower threshold values.